Transforming Arabic Language Learning in the Era of Artificial Intelligence: Opportunities and Challenges in Higher Education - Ahmad Nurul Huda Salmas; Zubaidah Zubaidah (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2026)
The rapid development of artificial intelligence (AI) has significantly transformed higher education, including Arabic language learning. This study critically examines the role of AI, particularly large language models, in reshaping learning processes, focusing on pedagogical, cognitive, and epistemological dimensions. Using a qualitative library research approach, this study analyzes recent scholarly works (2020–2025). The findings show that AI enhances access to linguistic input, enables personalized learning, and provides immediate feedback that improves learning efficiency. However, it also introduces challenges such as cognitive dependency, reduced depth of critical thinking, and concerns over knowledge validity, especially in Arabic learning, which is closely linked to Islamic intellectual traditions.The study further reveals that AI is more effective in supporting reading and writing skills than speaking and listening, due to the absence of authentic social interaction. From an epistemological perspective, AI cannot replace the interpretative authority of teachers. This study proposes a hybrid learning model that positions AI as a cognitive support tool rather than a substitute for human instruction, emphasizing the need for balanced integration between technology, pedagogy, and academic integrity.